2016
DOI: 10.7287/peerj.preprints.2570
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Avian community structure and habitat use of Polylepis forests along an elevation gradient

Abstract: Background. As one of the highest and most unique systems in the world, Polylepis forests are recognized both as center of endemism and diversity along the Andes and as a system under serious threat from human activities, fragmentation, and climate change. Effective conservation efforts are limited, in part, by our poor understanding of the habitat needs of the system’s flora and fauna. Methods. In 2014-2015, we studied bird communities and 19 associated local and landscape attributes within five fores… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
1
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 0 publications
1
15
1
1
Order By: Relevance
“…Besides showing direct responses to fragment size in their abundances (Lloyd 2008 b ), both species respond to habitat and tree quality, with positive impacts of larger trees as these contain relatively more arthropods as a food resource. Giant Conebill was previously known to be more abundant, and to have smaller home ranges, at sites with a high density of large, mature trees (Cahill and Matthysen 2007, Lloyd 2008 b , De Coster et al 2009, Sevillano‐Ríos and Rodewald 2017, Astudillo et al 2020), but we now show that the bird indeed preferentially forages on larger trees, and this more often so in large fragments, in response to higher arthropod density. Some other insectivorous birds have also been shown to select trees based on arthropod density for increased foraging efficiency.…”
Section: Discussionsupporting
confidence: 44%
See 2 more Smart Citations
“…Besides showing direct responses to fragment size in their abundances (Lloyd 2008 b ), both species respond to habitat and tree quality, with positive impacts of larger trees as these contain relatively more arthropods as a food resource. Giant Conebill was previously known to be more abundant, and to have smaller home ranges, at sites with a high density of large, mature trees (Cahill and Matthysen 2007, Lloyd 2008 b , De Coster et al 2009, Sevillano‐Ríos and Rodewald 2017, Astudillo et al 2020), but we now show that the bird indeed preferentially forages on larger trees, and this more often so in large fragments, in response to higher arthropod density. Some other insectivorous birds have also been shown to select trees based on arthropod density for increased foraging efficiency.…”
Section: Discussionsupporting
confidence: 44%
“…Both insectivorous species forage primarily on bark‐dwelling arthropods from Polylepis trees; C. binghami selects mature trees and forages primarily on tree trunks by prying in the bark, whereas S. yanacensis forages on twigs and small branches (Lloyd 2008 a , Matthysen et al 2008). Previous studies have shown that their abundance is lower in smaller fragments and near fragment edges, like in other Polylepis bird specialists too (Cahill and Matthysen 2007, Lloyd 2008 b , Sevillano‐Ríos and Rodewald 2017). However, it is unclear if and to what extent this is related to habitat quality (i.e., lower abundance of food resources) or fragment size.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…In addition, we modelled the environmental associations of adult presence/absence of each Polylepis species within our study areas using the information from our sample plots and an additional 130 points sampled for vegetation structure by Sevillano‐Ríos and Rodewald (). This dataset covered an elevational range of 3300–4700 m in five valleys on the western side of HNP, including the four sampled for seedlings.…”
Section: Methodsmentioning
confidence: 99%
“…We studied bird communities in five glacial valleys of Cordillera Blanca, within Huascaran National Park and Biosphere Reserve, Ancash, Peru (9°06′19″S, 77°36′21″ W) [see 68 and 69 for a more detailed description]. This area is recognized as a center of avian endemism and diversity of the High Andes [42,[70][71][72] and contains some of the largest remaining areas and patches of Polylepis forest in the world [47,73]. The five glacial valleys (Parón, Llanganuco, Ulta, Llaca and Rajucolta) are located on the western slope of Cordillera Blanca and discharge into the Santa River and the Pacific Ocean (Figure 2).…”
Section: Study Areamentioning
confidence: 99%